Enterobacter strain 9410-O with porous substrates to enhance heterotrophic activity in bottom water environment - Karim, Md Abdul; Fukami, Kimio (Bangladesh Journal of Botany, 2010)
Mesophilic Enterobacter strain 9410-O isolated from a eutrophic bottom water environment and introduced into it to enhance heterotrophic activities and decompose organic matters in situ. The bacteria were added as cell suspension after absorbing with porous substrates, like Eco-breath, Neo-coal and Accela- 35. The strain stimulated net regeneration of dissolved inorganic nitrogen and inorganic phosphorus from the sediment by approximately three to fourfolds at 21 and 23° C, respectively. It appears that the application of Enterobacter strain 9410-O with Neo-coal as substrate would be promising for the purification of eutrophic bottom water environment. Key words: Enterobacter; Bottom environment; Porous substrates; Nitrogen; Phosphorus DOI: 10.3329/bjb.v38i1.5126 Bangladesh J. Bot. 38(1): 71-76, 2009 (June)